Federal Agency R&D Contract Awards and the FASB Rule for Privately-Funded R&D - Horwitz, Bertrand; Normolle, Daniel (The Accounting Review, 1988)
[This study examines the contention that a change in the method of financial reporting for privately-funded research and development (Statement of Financial Accounting Standards No. 2 and Securities and Exchange Commission Accounting Series Release No. 178) may have affected the ability of small high-technology firms to secure federal agency contract awards for R&D. Even though cash flows were not changed, many of these firms had significantly negative changes in the accounting levels and ratios used by federal agency analysts in evaluating financial capability of contract bidders as part of a preaward survey. ANOVA and ANCOVA models on a set of 101 research-intensive firms, with under $100 million of sales in 1975 and analyzed over the time period 1970-1979, did not detect an effect on the dollar amounts of the awards. Also, a matched-pair comparative study did not demonstrate any significant differences between expensing (unaffected) and deferring (affected) firms. Based upon these results, it is concluded that there is no evidence that the R&D rule reduced the amount of R&D awards by federal agencies to small research-intensive companies.]